2006
DOI: 10.3349/ymj.2006.47.5.614
|View full text |Cite
|
Sign up to set email alerts
|

Effects on Weight Reduction and Safety of Short-Term Phentermine Administration in Korean Obese People

Abstract: The phentermine, an appetite suppressant, has been widely applied in Korea since 2004. However, there have been relatively few reports about the efficacy and the safety of phentermine in Korea. The aim of this study is to verify the effect of phentermine on weight reduction and the safety in Korean patients. This randomized, double-blind, placebocontrolled study had been performed between February and July, 2005, in Seoul on 68 relatively healthy obese adults whose body mass index was 25 kg/m 2 or greater. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
49
1
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(56 citation statements)
references
References 17 publications
5
49
1
1
Order By: Relevance
“…The drug stimulates primarily the release of norepinephrine, but to lower extent also dopamine and serotonine. Depending on the dose (which is typically between 30 and 37.5 mg/d) the placebo-subtracted weight loss attributed to treatment with phentermine (30 mg/d) is in the range of 4-8 kg after 12 weeks of treatment (Kim et al, 2006;Kang et al, 2010;Moldovan et al, 2016). Phentermine is generally well tolerated with little to no abusive potential, even when used chronically for up to 21 years (Hendricks et al, 2009).…”
Section: B 24-dinitrophenolmentioning
confidence: 99%
“…The drug stimulates primarily the release of norepinephrine, but to lower extent also dopamine and serotonine. Depending on the dose (which is typically between 30 and 37.5 mg/d) the placebo-subtracted weight loss attributed to treatment with phentermine (30 mg/d) is in the range of 4-8 kg after 12 weeks of treatment (Kim et al, 2006;Kang et al, 2010;Moldovan et al, 2016). Phentermine is generally well tolerated with little to no abusive potential, even when used chronically for up to 21 years (Hendricks et al, 2009).…”
Section: B 24-dinitrophenolmentioning
confidence: 99%
“…In contrast, data from early clinical trials either did not mention blood pressure changes (6), suggested a low occurrence of hypertension during phentermine pharmacotherapy (7), or showed significant reductions in blood pressure and HR (8). A recent phentermine clinical trial reported slight decreases in blood pressure but made no mention of HR (9). A 1‐ or 2‐year long clinical trial of phentermine monotherapy could provide the data needed to clarify the effect of phentermine monotherapy on blood pressure and HR but no such trial of phentermine has been conducted.…”
Section: Introductionmentioning
confidence: 99%
“…The most frequent AEs reported in this study included insomnia (11.0%) and dry mouth (5.6%). Some domestic studies have reported that dry mouth is the most commonly observed AE, while foreign studies often cite headache as the most common 12,14). Although pulmonary hypertension,15) hypertrophic cardiomyopathy,16) and ischemic stroke have been reported as serious AEs following the administration of amphetamine-like analogues, such as phendimetrazine, these rare AEs were not reported in this study.…”
Section: Discussionmentioning
confidence: 62%